The Importance of Parental Guidance in the Development of Independence in Early Childhood - Fitri, Ulfa Hasanatul; Ismaniar, Ismaniar (Universitas Negeri Padang, 2025)
This study is driven by the reality that numerous issues reemain in the fostering independence during early childhood development. This can be seen from the daily lives of children. This research is focused on highlighting the role of parental support in fostering independence during early childhood development. The approach used in this study is a review of existing literature, namely by reviewing various sources such as scientific journals, books, and previous research that are relevant to the topic. The topic analyzed in this study is the still low development of independence in early childhood and how parental guidance in the development of independence in children will affect children. The findings of the research indicate that (1) children can cultivate independence early in life, depending on their age and development objectives, like eating by themselves and puutting on their own footwear (2) parents have a role and duty in guiding the development of independence in children from an early age. So, through parental guidance, children can become independent, responsible for what they have and become confident in carrying out activities without help from others. It is hoped that parents can provide time to provide stimulation to children from an early age.